HUBUNGAN JANGKA PENDEK DAN JANGKA PANJANG DI ANTARA FDI, EKSPOR DAN PDB - Sundoro, Hary Saputra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
A global trade war is expected to impact the economy of every country. The purpose is to examine relationship between FDI, Exports and GDP during global trade war. It is hoped that the stakeholders, especially the government, can take the necessary actions. The research method used is VECM with quarterly analysis starting from 2010 to 2019. The result shows that there is a positive relationship between Exports and GDP in the short and long term. During the era of the global trade war, foreign investment will be more horizontal in nature with the aim of market sharing. Thus, there is a negative relationship between FDI with exports and GDP in Indonesia. The implication of this research is that the government must make policies that can attract FDI more vertically. Therefore, FDI will be prioritized for the exploration of inputs where output will be exported outward and GDP will also rise